Rate of force development in the quadriceps of individuals with severe knee osteoarthritis: A preliminary cross-sectional study - Suzuki, Yusuke; Iijima, Hirotaka; Nakamura, Masatoshi; Aoyama, Tomoki (PloS one, 2022)
Knee osteoarthritis (KOA) is a leading cause of knee pain and disability due to irreversible cartilage degeneration. Previous studies have not identified modifiable risk factors for KOA. In this preliminary cross-sectional study, we aimed to test the following hypotheses: individuals with severe KOA would have a significantly lower quadriceps rate of force development (RFD) than individuals with early KOA, and the decrease in quadriceps RFD would be greater than the decrease in maximum quadriceps strength in individuals with severe KOA. The maximum isometric strength of the quadriceps was assessed in individuals with mild (Kellgren and Lawrence [K&L] grade 1–2) and severe KOA (K&L grade 3–4) using a handheld dynamometer. The RFD was analyzed at 200 ms from torque onset and normalized to the body mass and maximum voluntary isometric contraction torque. To test whether the quadriceps RFD was lowered and whether the lower in the quadriceps RFD was greater than the lower in maximum quadriceps strength in individuals with severe knee OA, the Mann–Whitney U-test and analysis of covariance were performed, respectively. The effect size (ES) based on Hedges’ g with a 95% confidence interval (CI) was calculated for the quadriceps RFD and maximum quadriceps strength. Sixty-six participants were analyzed. Individuals with severe KOA displayed significantly lower quadriceps RFD (p = 0.009), the lower being greater than the lower in maximum quadriceps strength (between-group difference, ES: 0.88, -1.07 vs. 0.06, -0.22). Our results suggest that a decreased quadriceps RFD is a modifiable risk factor for progressive KOA. Our finding could help in the early detection and prevention of severe KOA.